Worker’s Personal Exposure to PM0.1 and PM4 Titanium Dioxide Nanomaterials during Packaging - Ichiro Higashikubo; Rizki Andre Handika; Toshihiro Kawamoto; Hidesuke Shimizu; Thunyapat Thongyen; Suthida Piriyakarnsakul; Amin Muhammad; Mitsuhiko Hata; Masami Furuuchi (Aerosol and Air Quality Research)
Abstract For the appropriate hygienic management of workplaces where workers handled nano-TiO2 products, the status of the personal exposure of workers to respirable dust (PM4) and nanoparticles (PM0.1) was investigated. Using a cyclone sampler for PM4 and a personal sampler for PM0.1, PM4 and PM0.1 exposure levels were evaluated to discuss them in relation to worker’s duties. The number of particles of 0.01–10 µm was also monitored online in order to examine the short-term fluctuation in the concentration and size distribution of particles. The 8h-time-weighted average (TWA) and 95% upper limit for respirable dust exposure were below the occupational exposure limit specified by the Japan Society for Occupational Health and the recommended exposure limits for TWA by NIOSH. The action level was exceeded during the filling of a flexible container bag. More than 70% of particles in the breathing zone was coarse agglomerates of > 1 µm, while it may be influenced by powder properties and the handling process as well as the management of local ventilation. The maximum PM0.1 concentration (31.3 µg m–3) occurred in a powder filling booth without air ventilation. The operation of a gasoline powered forklift temporarily increased the concentration of ultrafine particles. Most of TiO2 powder was suspended as micron-order agglomerates in the breathing zone. However, since PM0.1 exposure was much larger than those in outdoor environment particularly under insufficient cares to aerosolized powder and air ventilation, PM0.1 exposure should also be monitored.